Calvin's ecclesiology : a study in the history of doctrine - Maruyama, Tadataka (Grand Rapids William B. Eerdmans Publishing Company, 2022)
"A major study of John Calvin's conception of the church that traces his evolving thought throughout the course of his life and writings"--
"In this fresh and original monograph on the ecclesiology of John Calvin, Tadataka Maruyama sifts exhaustively through the corpus of Calvin's writings-in both Latin and French-to crystalize the French reformer's conception of the Christian church. After elucidating Calvin's influence from other reformers such as Jacques Lefèvre, Guillaume Farel, and Martin Bucer, Maruyama shows how Calvin's ecclesiology evolved throughout his life while remaining firmly rooted in key principles and interests. Maruyama discerns three phases in Calvin's ecclesiology:Catholic ecclesiology-in which Calvin saw the church as a unified and ideal institution situated both above and within historyReformed ecclesiology-in which Calvin described the concrete, historical form of the Christian church over against the Catholic ChurchReformation ecclesiology-in which Calvin came to understand the Christian church as an eschatological reality situated in a broader European context, which Calvin portrayed as the "theater of God's providence"This trajectory mirrors the way the Protestant Reformation was focused on reforming particular churches while also reimagining the Christian world as a whole. Indeed, as Maruyama thoroughly illustrates, Calvin never lost sight of his original vision of reforming the church of his French homeland even as his work grew into a much larger movement"--
Includes bibliographical references (pages 445-459) and indexes.
Keywords: Calvin, Jean, -- 1509-1564.; Church -- History of doctrines -- 16th century; RELIGION / Christian Theology / Ecclesiology; HISTORY / Europe / Renaissance